Nanoscale science and technology with plant viruses and bacteriophages - Bittner, Alexander M; Alonso, José María; Górzny, Marcin L; Wege, Christina (Sub-cellular biochemistry, 2013)
Nanoscale science refers to the study and manipulation of matter at the atomic and molecular scales, including nanometer-sized single objects, while nanotechnology is used for the synthesis, characterization, and for technical applications of structures up to 100 nm size (and more). The broad nature of the fields encompasses disciplines such as solid-state physics, microfabrication, molecular biology, surface science, organic chemistry and also virology. Indeed, viruses and viral particles constitute nanometer-sized ordered architectures, with some of them even able to self-assemble outside cells. They possess remarkable physical, chemical and biological properties, their structure can be tailored by genetic engineering and by chemical means, and their production is commercially viable. As a consequence, viruses are becoming the basis of a new approach to the manufacture of nanoscale materials, made possible only by the development of imaging and manipulation techniques. Such techniques reach the scale of single molecules and nanoparticles. The most important ones are electron microscopy and scanning probe microscopy (both awarded with the Nobel Prize in Physics 1986 for the engineers and scientists who developed the respective instruments). With nanotechnology being based more on experimental than on theoretical investigations, it emerges that physical virology can be seen as an intrinsic part of it.